Current Aspects for Searching and Returning Assets: Problems and Perspectives for Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2021)
Numerous acts of corruption by high-ranking officials and abuse of power over the past ten years have been accompanied by large-scale withdrawals of illegally obtained funds from Ukraine abroad. Therefore, the strategic goal of the government was to build an effective system for searching and returning illegally obtained assets.The process of forming a system of special state agencies in the field of returning illegally obtained assets has recently covered the criminal procedural direction, while the work with such assets starting from their search up to return, can be carried out during civil proceedings.The work on searching and returning illegally obtained assets to Ukraine is currently characterized by increased complexity and lack of efficiency due to the imperfection of existing procedures and the constant improvement of the methods to remove them from the country.The general mechanism for returning corrupt assets is based on the requirements of the criminal procedural legislation of Ukraine and provides three stages: registration of criminal proceedings; sending an official appeal to the governments of foreign states with a request to freezing the assets; sending the request to initiate criminal proceedings related to the misappropriation of assets. All stages of this mechanism may have difficulties and obstacles due to shortcomings in the legislation on these issues and cooperation with foreign law enforcement agencies.The world practice of returning corrupt assets also indicates that the successful return of withdrawn assets requires the compliance with a number of conditions: the presence of political will of the state leadership to return assets; sufficient level of national legislation and its compliance with international standards; availability of the necessary internal potential of state agencies; establishment of interagency cooperation; taking into account the peculiarities of the legal systems of interacting countries; availability of international support.This is the reason why the formation of the system for searching and returning illegally obtained assets, creation of the necessary legislative preconditions and establishment of effective international cooperation are the priority tasks of the state. Proper functioning of such a system will demonstrate the inevitability of punishment for corruption crimes, will eliminate the sense of taking assets out of the country and, consequently, will help to prevent corruption crimes and offenses, will stabilize the economy by recovering illegally obtained funds.
Keywords: assets; illegally obtained; return of assets; problems; improvement; solution; world experience.